Physicochemical investigation of ultrasound effects on some steps of mink fur processing. A suggestion for improving the worker health and reducing the environmental impact. (1st February 2017) - Bufalo, Gennaro; Di Nezza, Francesca; Cimmino, Luciana; Cuomo, Francesca; Ambrosone, Luigi
Abstract: The tanning industry is considered a source of major environmental pollution and hazard to the health of workers. The greasing stage is mainly performed to improve the softness of leather while the degreasing one serves to optimize the distribution in fatliquoring leather and eliminate its excess. To produce mink fur commercially attractive the tanning-oil-greasing method is used, which requires a large excess of both grease and solvents. Tanning-alum-water greasing method which greatly simplifies machining cycles using less solvent in the degreasing stage could be harnessed. However, the fur absorbs only small tanning-greasing quantities resulting a poor quality product. Laboratory tests were carried out on mink fur to understand how to extend on a large scale the tanning-alum-water greasing method. Experimental results, obtained irradiating the soaking bath with ultrasound at different powers, show that the cavitation is triggered in the range of 20–30 W and develops for larger powers. Results provides the basis for changing the tanning-alum-water greasing method to produce mink fur in a single stage . Particularly, enhanced optical microscopy indicates that fat globule diameters are reduced by 50% whilst skin absorption improves by 25%. How to rearrange the method on large-scale is also discussed. The method, considered as a whole must be considered "best available technology" Graphical abstract: